Shortening intradermal rabies post-exposure prophylaxis regimens to 1 week: Results from a phase III clinical trial in children, adolescents and adults. - Phirangkul Kerdpanich; Pornthep Chanthavanich; Mari Rose De Los Reyes; Jodor Lim; Delia Yu; Ma Cecilia Ama; Zenaida Mojares; Daniela Casula; Ashwani Kumar Arora; Michele Pellegrini (Public Library of Science (PLoS), 2018)
This phase III clinical trial compared the immunogenicity and safety of a purified chick-embryo cell rabies vaccine (PCECV) administered according to a shortened post-exposure prophylaxis (PEP) 4-site/1-week intradermal regimen, compared with the currently recommended 2-site/Thai Red Cross (TRC) regimen.This controlled, open-label, multi-center study (NCT02177032) enrolled healthy individuals ≥1 year of age, randomized into 4 groups to receive intradermal PCECV according to one of the 2 regimens, with or without human rabies immunoglobulin (HRIG) administration at first visit (in adults only). Rabies virus neutralizing antibody (RVNA) concentrations and percentages of participants with RVNA concentrations ≥0.5 IU/mL (considered as adequate concentrations following PEP) were assessed up to day (D) 365 post-first vaccination. Non-inferiority of the 4-site/1-week regimen to the 2-site/TRC regimen was demonstrated if at D49, the lower limit of the 95% confidence interval (CI) for the difference between groups in the percentage of participants with adequate RVNA concentrations was >-5%. Of the 443 participants receiving the 4-site/1-week regimen, 88 adults received HRIG; 442 participants received the 2-site/TRC regimen (88 with HRIG). All participants achieved adequate RVNA concentrations by D14. At D49, the difference in percentage of participants with adequate RVNA concentrations between the 4-site/1-week and the 2-site/TRC groups was -1 (95%CI: -2.4-0.0); thus, non-inferiority was concluded. RVNA geometric mean concentrations were 18 IU/mL in 4-site/1-week groups and 12 IU/mL in 2-site/TRC groups at D14, and subsequently declined in all groups. RVNA concentrations were consistently lower in adults with HRIG administration than in those without. The 2 regimens had similar safety profiles. Of the 15 serious adverse events reported in 4-site/1-week groups and 19 in 2-site/TRC groups, none were vaccination-related.The data suggest that the 4-site/1-week regimen might be an alternative to current recommendations, with potential benefits in terms of improved cost-efficiency and compliance to vaccination.